Intracultural diversity - Holtbrügge, Dirk; Kirste, Laura (Elgar Encyclopedia of Cross-Cultural Management, 2024)
This entry highlights nuances of intracultural diversity, emphasising that within-country variations can surpass intercultural differences. It distinguishes three conceptual foundations: level-based, variance-based, and pattern-based. Level-based concepts attribute cultural differences to regional, state, or district variations within a country, employing frameworks such as Hofstede's dimensions. Variance-based concepts, such as Gelfand's tightness–looseness and ethno-linguistic fractionalisation, measure cultural diversity by accounting for within-country variations. Pattern-based concepts, exemplified by cultural archetypes, explore the combined configuration of cultural dimensions. It suggests managerial considerations, such as the impact of intracultural diversity on expatriates and its relevance in foreign acquisitions.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cultural differences; Diversity; Emic; Etic; Level-based; Pattern-based; Variance-based; Within-country differences